2020
DOI: 10.3390/cancers12040847
|View full text |Cite
|
Sign up to set email alerts
|

Lactotransferrin Downregulation Drives the Metastatic Progression in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the main type of RCC, which is the most common type of malignant kidney tumor in adults. A subpopulation (>30%) of ccRCC patients develop metastasis; however, the molecular mechanism remains largely unknown. Here, we found that LTF, the gene encoding lactotransferrin, is dramatically downregulated in primary tumors compared to normal tissues derived from ccRCC patients deposited in The Cancer Genome Atlas (TCGA) database and is a favorable prognostic marker. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…We found that most ductal cells were derived from the normal pancreas (89.08%, 563/632), whereas only 68 ductal cells were derived from the adjacent normal tissue of the PASC sample (Figure 2 A and B). Notably, these cells were “entangled,” expressing antitumor genes such as LTF 24 , oncogenes such as CXCL6 25 , SAA1 26 , and S100A9 27 , and the inflammation gene CRP. Therefore, we consider this cell type a transitional cell type between healthy ductal and PASC cells.…”
Section: Resultsmentioning
confidence: 99%
“…We found that most ductal cells were derived from the normal pancreas (89.08%, 563/632), whereas only 68 ductal cells were derived from the adjacent normal tissue of the PASC sample (Figure 2 A and B). Notably, these cells were “entangled,” expressing antitumor genes such as LTF 24 , oncogenes such as CXCL6 25 , SAA1 26 , and S100A9 27 , and the inflammation gene CRP. Therefore, we consider this cell type a transitional cell type between healthy ductal and PASC cells.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous report [ 24 ], we have demonstrated that a low-level LTF expression is associated with a high risk for cancer metastasis and poor prognosis in TCGA ccRCC patients. To ascertain a possible mechanism underlying the metastatic progression of ccRCC with LTF downregulation, here we firstly performed a computational simulation using the Gene Set Enrichment Analysis (GSEA) program.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the simulation, we generated two LTF-related gene sets derived from the TCGA ccRCC database and GSE36972 dataset. We generated one of LTF-related gene sets by performing LTF coexpression status that was ranked by Spearman’s correlation test with other somatic genes included in RNA sequencing experiment against primary tumors derived from TCGA ccRCC patients stratified as a low LTF-expression group in a Kaplan-Meier analysis [ 24 ] and recorded as lymph node metastasis ( Figure 1 A). On the other hand, we generated the other LTF gene set which was ranked by a log2 fold change of mRNA levels for all somatic genes in the LTF-overexpressing cells as compared to vector control cells in the GSE36972 dataset ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from transgelin, 16 other proteins were identified as up-regulated in sunitinib non-responsive mccRCC. Of these, 10 proteins were previously reported to have associations with renal tumorigenesis: an elevated level of lactotransferrin (LTF) was reported in non-responsive mccRCC tumors; however, LTF was observed to block metastasis in ccRCC in other studies [ 50 , 51 ]. Clusterin was elevated in acquired resistance to sorafenib, another rTKI drug, in a mouse model [ 52 ] and it promoted the growth and invasion of RCC cells in vitro [ 53 ].…”
Section: Discussionmentioning
confidence: 99%